Labour market friction effect on corporate performance : evidence in the global market : a dissertation submitted in fulfilment of the requirements for the degree of Doctor of Philosophy in Finance at Massey University, School of Economics and Finance, Massey University - Bai, Hengyu (Massey University, 2023)
This thesis represents the first academic endeavour to investigate the impact of labour market friction on corporate performance in a global context. In traditional neoclassical economic theory and relevant research, human capital was considered merely an input to generate economic value. Unemployed workers were assumed to fill vacant job positions perfectly, similar to interchangeable machine parts. However, as understanding has evolved, economists now recognise the complexities of filling a job vacancy, which needs to take into account the skills, geographic locations, labour preferences, and various objective factors of the labour force. Consequently, a mismatch often occurs between unemployed workers and vacant jobs, resulting in simultaneous unemployment and job vacancies. This phenomenon is termed labour market friction. This thesis comprises three subprojects, each contributing a distinct essay. The first essay examines the effect of labour market friction on expected stock returns in the Chinese stock market. Utilising the portfolio sorting approach and the Fama-MacBeth regression model, the findings indicate that firms with higher labour friction risk are likely to experience higher stock returns in the subsequent month. This suggests that labour friction risk serves as a significant risk factor in asset pricing. Additionally, the study reveals that the positive effect of labour friction on expected stock returns is more pronounced in firms with either high productivity or poor employee welfare. Furthermore, firms in regions with high levels of development are more likely affected by the labour friction risk. The second essay expands the scope from the Chinese stock market to global stock markets, including North America, Asia-Pacific, and Europe. The results reveal regional variations in the impact of labour market friction on expected stock returns. Specifically, labour friction risk has a negative association with expected stock returns in North American markets, whereas it is positively correlated in Asia-Pacific markets. The significant labour market friction effects are pronounced in different industries due to the varieties of labour market structures, where the North American markets contain a large partial of high technology companies, while the Asia-Pacific markets are dominated by numerous industrial companies. There is no significant relationship between labour friction risk and expected stock returns in European markets. The study also finds that the effect of labour friction is particularly pronounced in markets that are non-immigrant or non-English-speaking, providing higher external labour supply and mobility in such markets, which reduces firms’ recruitment pressures. The third essay centres on Corporate Social Responsibility (CSR) behaviours under the influence of labour market friction in a global setting. The results suggest that firms facing higher labour friction risks are more inclined to engage in CSR activities, even when controlling for year, industry, and region effects in the regression model. This CSR engagement is notably more prominent in markets with a higher demand for labour, characterised by a higher number of new businesses and job vacancies. These findings remain consistent across markets that encourage business creation and expansion through strong investor protection and low labour taxation policies. Markets with higher levels of advanced education have a more significant labour market friction effect on CSR decision-making as they have numerous labour-intensive firms which require a large labour force. Additionally, when labour unions have the strong bargaining power to protect the welfare of employees, firms are less inclined to conduct CSR activities due to the less function in controlling the labour market friction risk. In summary, this thesis contributes to the existing literature by providing empirical evidence of the effects of labour market friction on corporate performance and behaviours across different global markets. It demonstrates that the impact of labour market friction varies due to differing labour market policies and structures and is significantly influenced by the dynamics of labour supply and demand. The insights derived from examining labour market friction across diverse markets have critical implications for both corporate managers and policymakers seeking to mitigate the associated risks.
Keywords: Labor market; Stocks; Prices; Corporations; Valuation; China; Social responsibility of business; labour market friction, asset pricing, CSR; 350202 Finance